The radio spectrum of the galaxy - Burke, B.P. (1968)
The progress of human knowledge often seems to come in sudden bursts of activity, with resting periods in between, when the new concepts are exploited, fitted into existing pictures of the physical world, or the pictures of the world modified to fit the new insights. In astrophysics, radio spectroscopy may well be in the midst of such an active phase. Two decades have passed since van de Hulst suggested, in 1904, that the ground state hyper-fine transition in Hydrogen, the celebrated 21-cm line, should be an exceptionally useful tool in studying the galaxy.